HDAC6 at Crossroads of Infection and Innate Immunity. Issue 8 (August 2018) - Moreno-Gonzalo, Olga; Mayor, Federico; Sánchez-Madrid, Francisco
Abstract : Histone deacetylase 6 (HDAC6) acts by enzyme-dependent and -independent mechanisms to regulate diverse cellular processes including autophagy, the ubiquitin proteasome system, and cell migration. HDAC6 also has emerging roles in innate immunity, including pathogen sensing and destruction, thus placing this enzyme at the crossroads of infection and innate immunity.